FHIR 2.0: Beyond Interoperability to AI-Ready Healthcare Ecosystems - Bapatla, Sai Krishna Sandilya (International Journal of Computing and Engineering, 2025)
The Fast Healthcare Interoperability Resources (FHIR) standard has been a game-changer in tackling the ongoing fragmentation issues facing the healthcare sector. The development of FHIR from a simple interoperability framework to the fundamental architecture for AI-driven healthcare ecosystems is examined in this article. Healthcare practitioners can share discrete data items without document-level overhead because of FHIR's modular resource-based design, which matches technical implementation with clinical conceptualization. Real-time data sharing is supported by FHIR's RESTful API framework, which greatly lowers integration complexity while enhancing system efficiency by utilizing well-known web protocols. The standard effectively creates unified data representations that improve workflow efficiency and minimize unnecessary data entry by bridging the previously divided clinical and administrative domains. At the same time, FHIR's subscription mechanisms allow real-time data streams that power predictive applications, and its standardized format offers the semantic consistency required for machine learning applications. Through terminology mapping services, interface engines, and extensive security protocols, FHIR continues to show significant benefits despite implementation problems such as semantic harmonization, legacy system integration, and regulatory compliance requirements. FHIR is the crucial foundation supporting the upcoming generation of sophisticated healthcare apps as healthcare digitization speeds up.